Accessible Tourism through Digital Accessibility for 2030 Agenda for Sustainable Development. Are We Ready for WCAG 3.0? - Elena Fernández-Díaz; Nelson de Matos; Marisol B. Correia (Journal of Tourism, Sustainability and Well-being)
Tourism for all, and especially accessible tourism, is a generalized social demand that must be made possible by public authorities and companies in some way linked to the provision of tourist services. International regulations on digital accessibility are advancing so quickly that in just 5 years they have been updated 3 times, and the Web Content Accessibility Guidelines (WCAG) 3.0 draft is currently in place to face the technological challenges of the future. It applies flexibly to all kinds of content, apps, tools, publications and emerging technologies. The importance of this research is determined to learn more about compliance with digital accessibility in the tourism industry. A Systematic Quantitative Literature Review (SQLR) is applied with searches in WoS and Scopus, with a total of 28 articles analyzed from 1999 to 2021 period, using the search strings: “web accessibility” or “accessible tourism”. Results show that digital accessibility is a pending issue in this sector with significant accessibility problems or ignorance about its importance by the public involved in the tourism industry. It provides a vision on the future of digital accessibility in the tourism sector and designs a research agenda with the WCAG, the stakeholders and channels that influence in their environment.